2017
DOI: 10.1016/j.diagmicrobio.2017.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Capnophilic Enterobacteriaceae

Abstract: Bacteria use bicarbonate as substrate for crucial metabolic reactions. We report the first case of bacteremia by capnophilic E. coli without the YadF gene (also known as CynT2 or Can2) that needs high concentrations of CO to non-enzymatically produce bicarbonate. This lack may also apply to previously reported capnophilic Enterobacteriaceae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Whole genome sequencing analysis by the MiSeq® system (Illumina, San Diego, USA) was performed to inspect assumed genes that contained previously-reported causative mutations for the E. coli SCV phenotype ( hemB , menC , and lipA gene) [ 1 , 5 ], but no genetic mutational variations were observed between the two strains. The yadF gene was not present in either strain, which is consistent with previous reports about capnophilic E. coli strains [ 6 ].…”
Section: Case Reportsupporting
confidence: 92%
“…Whole genome sequencing analysis by the MiSeq® system (Illumina, San Diego, USA) was performed to inspect assumed genes that contained previously-reported causative mutations for the E. coli SCV phenotype ( hemB , menC , and lipA gene) [ 1 , 5 ], but no genetic mutational variations were observed between the two strains. The yadF gene was not present in either strain, which is consistent with previous reports about capnophilic E. coli strains [ 6 ].…”
Section: Case Reportsupporting
confidence: 92%
“…Sahuquillo-Arce et al (10) recently showed that the can gene of the 2 capnophilic E. coli strains cannot be detected by PCR. Likewise, the can gene of P. mirabilis NA2609 was undetectable by PCR, although the can genes of ATCC 29906 and the 2 clinical strains were amplifiable.…”
mentioning
confidence: 99%